Preliminary evaluation of the endovascular treatment of intracranial aneurysms with detachable coils in vigil patients - Fonseca, José Roberto Falco [UNIFESP] (2006)
Endovascular treatment of intracranial aneurysms with coil embolization became the most important therapeutic option with better morbidity and mortality rates and quality of life. Following immobility, patients are treated with general anaesthesia. OBJECTIVE: To test viability of endovascular treatment on wake patients. METHOD: Considering clinical symptoms, psychological characteristics and aneurysmal morphology, four patients with five intracranial aneurysms were selected. RESULTS: Four among five cases were completed with this technique. Patient 1 was partially treated after 75 minutes presenting vesical stress. Patient 2 presented subarachnoid hemorrhage after aneurysmal re-rupture, and the procedure was completed under general anaesthesia. The other three patients presented no intercurrences during the treatment. CONCLUSION: Endovascular treatment on wake patients with intracranial aneurysm can be an alternative to a selected group of patients.